Tracking protein turnover and degradation by microscopy: photo-switchable versus time-encoded fluorescent proteins - Knop, Michael; Edgar, Bruce (Open biology, 2014)
Expanded fluorescent protein techniques employing photo-switchable and fluorescent timer proteins have become important tools in biological research. These tools allow researchers to address a major challenge in cell and developmental biology, namely obtaining kinetic information about the processes that determine the distribution and abundance of proteins in cells and tissues. This knowledge is often essential for the comprehensive understanding of a biological process, and/or required to determine the precise point of interference following an experimental perturbation.
Gesehen am 09.08.2017